Saco .: Sustainable, authentic, convenient, organic: Terminal year end report - Jingco, Mary Angelei M. (Animo Repository, 2022)
As part of the course requirements of BS-Entrepreneurship, a young social enterprise was created and operated in a year which addresses environmental issues in society. This paper presents the plans and highlights of operations during the first year of the business. SACO is a social enterprise that envisions promoting the elimination of single-use products which harm biodiversity through producing eco-friendly products for the sustainable development of our planet. As of 2015, the solid waste diversion rate in Metro Manila alone numbers 48 percent compared to 46 percent outside the metro (PH GOV, 2017). Some areas are not given sufficient garbage collection which results in uncollected waste ending up in rivers, esteros, and other water bodies, thus polluting major water bodies and clogging the drainage systems. Moreover, the cumulative global plastics production has already reached 7 billion tonnes in the year 2015, which continues to increase up to today (Ritchie & Roser, 2018). Since most single-use wastes are hard to decompose and not suitable for long-term and everyday use, these wastes end up in oceans and landfills. The most significant issue here is that not everyone is aware of these issues, and those who are limited in their ability to act. As a solution, the company uses the method of upcycling reusable materials that can help lessen this issue especially when being able to dispose of single-use plastics.